Species richness prediction and priority conservation planning for rare Michelia species in China - Jimin Tang; Zhi Chen; Xiaojie Yin; Jiao Teng; Weijie Gao; Yifei Liu; Xiuyu Li (Scientific Reports)
Abstract Numerous species are at risk of extinction due to habitat degradation caused by human activity and global warming. This study is based on ecological niche modeling (MaxEnt) and systematic conservation planning modeling (Marxan) to predict the distribution and conservation of rare Michelia species. The findings indicate that rare Michelia species are found in southern Yunnan Province, which exhibits the highest concentration. The high richness zones are expected to shrink to 0.62 × 104 km2 under future climate scenarios. Northern high latitudes and higher altitudes are expected to offer better habitats for the majority of rare Michelia species. With the intensification of climate change, it is anticipated that this migration will exceed 150 km. Priority conservation zones for rare Michelia species are primarily located in the southeastern part of the Tibet Autonomous Region, the south-central part of Yunnan Province, the central part of Sichuan Province, the western part of Chongqing Municipality, the southern part of Guizhou Province, the northern part of Guangxi Zhuang Autonomous Region, the southern part of Hunan Province, the northern part of Guangdong Province, the eastern and southern parts of Jiangxi Province, the northwestern part of Fujian Province, the southern part of Zhejiang Province, the central part of Taiwan Province, and the southwestern part of Hainan Province. These priority conservation zones account for only 0.86% of the land area of China, with 6.6 × 104 km2 of prioritized conservation zones not yet designated as nature reserves or parks. To effectively embody the principle that ‘green mountains are golden mountains,’ we recommend expanding conservation zones for rare Michelia species within designated priority zones and enhancing habitat conservation measures.